STUDY OF TRANSIENT PROCESSES OF THE CURRENT COLLECTOR OF MOTOR-CAR ROLLING STOCK - Anton V. Volkov; Sergey N. Ivliev; Pavel V. Venchakov (Измерение, мониторинг, управление, контроль, 2024)
Background. Railway transport, due to large volumes of traffic, must be serviced in a timely and high-quality manner. One of the main problems in the transportation process is the occurrence of an uncontrolled electric arc between the current collector and the contact wire. The article describes the importance of the problem of studying transients in the occurrence of an electric arc in DC and AC networks. The purpose of the study is to study the temporary transients of the parameters of the electric arc and to identify the natural features of its occurrence. Materials and methods. A mathematical model of the electric arc of the current "current collector – contact wire" using the Simulink Matlab package is considered. Results and conclusions. The occurrence of an electric arc is accompanied by transient current processes, the value of which can reach several hundred amperes, and these currents, together with the current consumed by the load, can damage the contact wire, burning it out. By analyzing the nature of the transition process, it is possible to predict the wear of the pantograph slide in the early stages, which will avoid negative consequences.